Formation of cross-linked glucose oxidase aggregates in mesocellular foams - Jung, Dirk; Paradiso, Michelangelo; Hartmann, Martin (Journal of Materials Science, 2009)
Enzyme immobilization into solid mesoporous inorganic supports is a promising strategy to enable their use in continuous-flow fixed-bed reactors. In this study, the formation of cross-linked enzyme aggregates (CLEAs) of glucose oxidase (GOx) in the pores of mesocellular foams (MCFs) was investigated. The enzymes can enter the ultra-large cavities connected through the smaller windows, where their agglomeration and cross-linking with glutardialdehyde (GA) will take place. After cross-linking, the diameter of the CLEAs is larger than the diameter of the pore entrance and, thus, the enzymes are trapped in the pores of the support. By varying the experimental parameters, the optimum conditions for the preparation of active and stable immobilized biocatalysts were determined with respect to the resulting activity and to the enzyme loading. It is found that the preparation is preferably performed at pH 5.0, with a time delay between GA and GOx addition of 2 h and a n (GA)/n (GOx)-ratio of more than 400.